THINK GLOBALLY, ACT LOCALLY! LINGUISTIC AS A PROMOTIONAL STRATEGY BY MULTI-NATIONAL FAST FOOD CHAINS : A CASE OF INDONESIA - Eka Septi Pradani (Vol. 2 No. 1 (2024): Proceeding of International Conference on Cultures & Language 2024, 2024)
This research discusses how international fast food chains employ glocal strategies to promote and localize their brands in Indonesia. International fast food chains primarily utilize advertisements in their target country's language. The aim is to analyze the language used in advertisements on their official Instagram accounts and to examine how local languages are employed during special events in Indonesia. This becomes an important strategy in promoting their products through the incorporation of local languages in advertisements. A qualitative research approach was employed to analyze advertisements and to answer the research questions. The theoretical framework is based on Robertson’s (1980) conceptions of universalizing and particularizing tendencies, and on Fernandez's (2009) theory of 'Cultural Glocality' with a few modifications. The top five international fast food chains, including McDonald's, Dominos, KFC, Burger King, and Pizza Hut, were chosen for this reason. This study analyzed advertisements from January to April 2024. The findings reveal that multinational fast food chains are more popular in Indonesia because of the language they employ in their advertisements to attract and convey their message to their customers. The data analysis reveals that glocal strategies include employing local language(s), code switching, location, cultural/religious events, and language aspects in advertising. Using local language allows them to promote their products while simultaneously localize their brand in Indonesia.